Treating comorbid insomnia in patients enrolled in therapist-assisted transdiagnostic internet-delivered cognitive behaviour therapy for anxiety and depression: A randomized controlled trial - M. Edmonds; V. Peynenburg; V. Kaldo; S. Jernelöv; N. Titov; B.F. Dear; H.D. Hadjistavropoulos (Internet Interventions, 2024)
Transdiagnostic Internet-delivered cognitive behaviour therapy (ICBT) for patients experiencing anxiety and depression can produce large improvements in symptoms. Comorbid insomnia is common among individuals seeking treatment for anxiety and depression, yet transdiagnostic ICBT rarely targets insomnia and many ICBT patients report that symptoms of insomnia remain after treatment. This trial explored the impact of including a brief intervention for insomnia alongside an existing transdiagnostic ICBT course that included brief weekly therapist assistance. Patients were randomly assigned to receive either the Standard transdiagnostic (n = 75) or a Sleep-Enhanced course (n = 142), which included information on sleep restriction and stimulus control. Intent-to-treat analyses using generalized estimating equation (GEE) showed significant, large reductions in all primary outcomes (insomnia: d = 0.96, 95 % CI [0.68, 1.24]; depression: d = 1.04, 95 % CI [0.76, 1.33]; and anxiety: d = 1.23, 95 % CI [0.94, 1.52]) from pre-treatment to post-treatment, with changes maintained at 3-months. Patients assigned to the Sleep-Enhanced course reported larger reductions in insomnia than patients in the Standard transdiagnostic course (Cohen's d = 0.31, 95 % CI [0.034, 0.60]) at post-treatment but no significant between-group differences in any of the primary outcomes were found at follow-up. Patient-reported adherence to sleep restriction guidelines (p = .03), but not stimulus control instructions (p = .84) was associated with greater reductions in insomnia symptoms during the course. Overall, patients who received the Sleep-Enhanced course were satisfied with the materials and most patients reported making sleep behaviour changes. The trial results demonstrate that including a brief intervention targeting insomnia can be beneficial for many patients who enroll in ICBT primarily for symptoms related to anxiety and depression.